The hermeneutic circle as a means of illustration of the understanding problem when teaching didactic communications - E. E. Neupokoeva; N. K. Chapaev (Russian State Vocational Pedagogical University, 2021)
Introduction. The digitalisation of the education system has increased the importance of acquiring digital competencies. At the same time, soft-competencies changed their structure and acquired a specific digital component. Didactic communications, based on the acquisition of all three groups of competencies - soft, hard and digital, have been changed, especially in the field of information technology. Those cognitive and communicative difficulties, which were previously easily solved with direct contact, now require special soft-competencies of the teacher. The processes of the search for solutions to problems and the formulation of such problems become more acute. There is an urgent need to find ways to solve the problem of raising the effectiveness of cognitive interactions. Therefore, one such way could be the method for analysing the leading type of cognitive interactions in training through a hermeneutic approach.The aims of the present research are the following: to reveal scientific and methodological aspects of application of the hermeneutic approach in didactic communications training for vocational teachers; to demonstrate the example of a graphical representation of the model of the hermeneutic circle concerning cognitive processes for studying regulatory texts; to form the main provisions for the theory of preparation for effective professional communications as a tool for acquiring workplace flexibility skills.Methodology and research methods. The theoretical and methodological component of the research is based on hermeneutic, system-activity and integrative approaches. The main research findings are drawn upon the cognitive theory (theory of cognitive processes). Empirical research data were obtained through the included observation method, as well as through testing among the trainees.Results. A hermeneutic circle model was demonstrated. Such a model is the basis of the authors' methodology for teaching didactic communications in the field of information technologies. The basics of the theory of preparation for effective professional communications were developed. A fundamental tool was described showing the effectiveness of the application of the hermeneutic approach. The publication discloses a mechanism for understanding and interpreting a user algorithm. For the first time, the hermeneutic circle model is presented for understanding and interpreting user instructions by people of socionomic professions. The obtained theoretical and practical results can be interpolated into any scientific sphere, which is studied in the framework of primary vocational education in university or college degree programmes.Scientific novelty. The publication considers the hermeneutic circle model as a visual image that illustrates the specifics of cognitive processes when studying user algorithms as the basis for information exchange in the field of IT. The model demonstrates the reasons for the appearance of "weaknesses" when providing training for teachers in didactic communications in the field of IT.Practical significance. Since the issue of teaching workplace flexibility skills remains open at the level of theoretical and practical tools, there are some prerequisites for its development. The publication can be recommended to educators involved in the development of integrative disciplines aimed at improving communication skills. The main theoretical provisions are considered through the example of didactic communications in the field of IT.